Karakteristik Yoghurt dan Kefir Yang Diproduksi Dari Susu Kuda - Nurliyani, Nurliyani (2014)
Lactose, lactoferin and lysozyme in mare milk were higher than cow and goat milk, that it will affect the resulting fermented milk products. This study aimed to evaluate the characteristics of fermented milk yoghurt and kefir made from mare milk. Mare milk used for produce of yoghurt and kefir were pasteurized at a temperature of 85o C for 30 minutes, respectively. Pasteurized milk for yoghurt group inoculated with three different kinds of starter: Lactobacillus bulgaricus, Streptococcus thermophillus, and the combination of Lactobacillus bulgaricus and Streptococcus thermophillus. Furthermore, each treatment of yoghurt group was incubatedat 40oC until a pH value of about 5.0. Pasteurized milk for kefir group inoculated with 2% kefir grains, then incubated at room temperature 12 and 24 hours. The characteristics of fermented milk was evaluated in their total amount of bacteria, lactose, acidity, pH and alcohol. The data were statistically analyzed by one-way ANOVA. The results showed that the best yoghurt characteristic was obtained by lactobacillus bulgaricus starter, whereas the different incubation time had no effect on kefir characteristics, except in their alcohol content.